The Effect of Ethanol Extract Turmeric Rhizome (Curcuma Longa) to Histologycal Structure of Rat Rectum Induced Dextran Sodium Sulphate (DSS) - Nikmah, Lidia Maziyyatun; Fajariyah, Susantin; Mahriani, M. (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2019)
Turmeric (Curcuma longa) is a plant that people use as a traditional medicine to treat some diseases such as: anti-inflammatory, antidiarrhea, antioxidants, hepatoprotector, and others. One of the main chemical compounds contained in turmeric and has a role as anti-inflammatory is curcumin. This study was conducted to determine the effect of ethanol extract of turmeric rhizome (Curcuma longa) on the histologycal structure of rat rectum induced by Dextran Sodium Sulphate (DSS). Wistar strain rats was divided into three groups: negative control group, positive control group (1% DSS), and DSS treatment group 1% + ethanol extract of turmeric rhizome dose 200mg/KgBB. DSS is given ad libitum, while ethanol extract of turmeric rhizome is given orally. We used paraffin method and Haematoxilyn Eosin staining to make the preparation organ. The data were analyzed using One Way ANOVA test, Duncan Multiple Range Test (DMRT) test, and correlation test. The result of this study is DSS administration has an effect on decreasing average of crypt, number of Goblet cell, and depletion of rectal mucous layer. While treatment of extract turmeric rhizome can increase height of crypt and number of Goblet cell in rectal mucosal layer of rat. Keywords: Extract of turmeric rhizome, DSS, rectum, Rattus norvegicus